Doamnele diplomaţiei româneşti: Elena Văcărescu (1864–1937) - George Lețu (Revista de Istorie și Teorie Literară)
Elena Văcărescu, worthy successor of patriot noblemen, has fulfilled the testament-impulse, received from her illustrious predecessor, Ienăchiţă Văcărescu, to contribute to “the honoring of the country”. The French language, sister of her native language, facilitated the entry, with greater ease, into the broad European environment, of thoughts, unrests, and hopes of the Romanian nation. A witness to the foundation of the League of Nations, Elena Văcărescu dreamed of establishing a universal harmony in which Romania will have a well-deserved place.